2024
DOI: 10.1007/s10639-023-12392-2
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of project-based learning in enhancing computational thinking among students: A meta-analysis of 31 experiments and quasi-experiments

Wuwen Zhang,
Yurong Guan,
Zhihua Hu

Abstract: In the context of our rapidly digitizing society, computational thinking stands out as an essential attribute for cultivating aptitude and expertise. Through the prism of computational thinking, learners are more adeptly positioned to dissect and navigate real-world challenges, poising them effectively to meet the exigencies of future societal landscapes. The paradigm of project-based learning, heralded as a potent educational methodology, significantly amplifies students' prowess in computational thinking. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Online Project-Based Learning draws upon constructivist theories, emphasizing active engagement, social interaction, and authentic experiences as catalysts for knowledge construction and skill development (Chang et al, 2024;Plews et al, 2024;Wijnia et al, 2024). According to Ismail et al (2024), McLaughlin et al (2024, and Zhang et al (2024), PjBL aligns with constructivist principles by situating learning within real-world contexts, where students collaborate to solve complex problems, apply theoretical concepts, and construct meaning through hands-on experiences. Additionally, sociocultural theory underscores the importance of social interaction and collaborative learning in cognitive development, highlighting the role of peers, mentors, and community members in scaffolding learning experiences within online PjBL environments (Al-Bahadli et al, 2023;do Amaral et al, 2023;Mielikäinen & Viippola, 2023;Zhong & Lyu, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online Project-Based Learning draws upon constructivist theories, emphasizing active engagement, social interaction, and authentic experiences as catalysts for knowledge construction and skill development (Chang et al, 2024;Plews et al, 2024;Wijnia et al, 2024). According to Ismail et al (2024), McLaughlin et al (2024, and Zhang et al (2024), PjBL aligns with constructivist principles by situating learning within real-world contexts, where students collaborate to solve complex problems, apply theoretical concepts, and construct meaning through hands-on experiences. Additionally, sociocultural theory underscores the importance of social interaction and collaborative learning in cognitive development, highlighting the role of peers, mentors, and community members in scaffolding learning experiences within online PjBL environments (Al-Bahadli et al, 2023;do Amaral et al, 2023;Mielikäinen & Viippola, 2023;Zhong & Lyu, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…b. Collaboration: Collaborative inquiry and teamwork are central to PjBL, enabling students to leverage diverse perspectives, skills, and resources to achieve shared goals (Lyu et al, 2023;Zhang et al, 2024). c. Inquiry: PjBL encourages inquiry-driven exploration, where students pose questions, conduct research, and generate solutions through self-directed investigation (Guo et al, 2022;Plews et al, 2024) d. Reflection: Reflective practices promote metacognition and deep understanding by encouraging students to critically evaluate their learning processes, outcomes, and areas for growth (do Amaral et al, 2023;Hao et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have emphasized the importance of authentic tasks, inquirybased learning, and collaboration in PjBL, highlighting its alignment with constructivist and sociocultural learning theories (do Amaral et al, 2023;Plews et al, 2024). Studies have shown that students engaged in PjBL projects demonstrate improved academic performance, higher motivation, and enhanced problem-solving skills than those in traditional classrooms (Abuhmaid et al, 2020;Cai et al, 2023;Zhang et al, 2024). Furthermore, research has identified various models and frameworks for designing and implementing PjBL, such as the Buck Institute for Education's (BIE) Gold Standard PBL model and the framework proposed by Thomas in Wijnia (Wijnia et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends in PjBL research include a focus on integrating technology, fostering equity and inclusion, and promoting interdisciplinary collaboration (Crawford et al, 2024;McLaughlin et al, 2024;Zhang et al, 2024;Zhong & Lyu, 2022). Researchers have explored innovative ways to leverage technology to enhance PjBL experiences with the widespread adoption of digital tools and online platforms.…”
Section: Introductionmentioning
confidence: 99%